T-standpoint assists the waiting of predatory birds in lucerne - Simunić, Ana-Marija (Array, 2020)
Field rodents can cause considerable economic losses in perennial crops, especially lucerne. Predatory birds can provide biological control of field rodent populations. However, modern arable landscape usually provides few or no natural standpoints for predatory birds to wait for their prey. According to the old farmers in eastern Croatia, T-standpoints installed into lucerne were traditional implements assisting the bird predation over field rodents. Aim of this study was to check whether the T-standpoints really are appropriate installations for the predatory birds to wait for their prey on the ground or not. The research has confirmed that predatory birds (Buteo buteo and Falco tinnunculus) descended on the installed T-standpoints (in average 1.35 arrivals per day of observation), waited (average period of stay was 17 minutes in the morning and 34 minutes in the afternoon) and landed on the ground, most probably to catch the prey (in average 13 % of arrivals to T-standpoints ended with landing to the ground, likely for the prey attack). Small forest restoration in arable landscapes and less chemical rodent control would probably improve the predatory bird populations, thus enhancing the biological control of field rodents. There remains the need for further investigation of efficiency of field rodent control by predatory birds.